Exome array analysis of rare and low frequency variants in amyotrophic lateral sclerosis - Dekker, Annelot M.; Diekstra, Frank P.; Pulit, Sara L.; Tazelaar, Gijs H. P.; van der Spek, Rick A.; Van Rheenen, Wouter; van Eijk, Kristel R.; Calvo, Andrea; Brunetti, Maura; Damme, Philip Van; Robberecht, Wim; Hardiman, Orla; et al. (Scientific reports, 2019)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that affects 1 in ~350 individuals. Genetic association studies have established ALS as a multifactorial disease with heritability estimated at ~61%, and recent studies show a prominent role for rare variation in its genetic architecture. To identify rare variants associated with disease onset we performed exome array genotyping in 4,244 cases and 3,106 controls from European cohorts. In this largest exome-wide study of rare variants in ALS to date, we performed single-variant association testing, gene-based burden, and exome-wide individual set-unique burden (ISUB) testing to identify single or aggregated rare variation that modifies disease risk. In single-variant testing no variants reached exome-wide significance, likely due to limited statistical power. Gene-based burden testing of rare non-synonymous and loss-of-function variants showed NEK1 as the top associated gene. ISUB analysis did not show an increased exome-wide burden of deleterious variants in patients, possibly suggesting a more region-specific role for rare variation. Complete summary statistics are released publicly. This study did not implicate new risk loci, emphasizing the immediate need for future large-scale collaborations in ALS that will expand available sample sizes, increase genome coverage, and improve our ability to detect rare variants associated to ALS.
Gesehen am 17.06.2021